Electrochemistry and Antioxidant Activities of Substituted Furanyl Nitrone: The Role of the Nitro Group - Danyelle Cândido Santos; Débora de Souza dos Santos Costa; Paulo R. R. Costa; Ayres Guimarães Dias; Messias de Oliveira Silva; Taualia Achira Aly; Vinícius Del Colle; Jadriane Almeida Xavier; Marília O. F. Goulart; Thaissa Lúcio Silva (ChemElectroChem, 2025)
This work compares electrochemical and antioxidant data for synthetic furfural‐derived nitrone (LQB‐109), the novel N‐methyl‐nitroaryl‐furanyl‐nitrone (LQB‐569), and the parent aldehyde (5NBFAL). Cyclic voltammograms (CVs) are obtained on a glassy carbon electrode (GCE) in acetonitrile (MeCN) and 0.1 mol L−1 n‐Bu4NPF6 versus Ag|AgCl|Cl−, to evaluate cathodic and anodic behavior and chemical processes. The CVs of LQB‐109 display two irreversible cathodic waves at −2.04 V and − 2.19V, related to a four‐electron reduction to hydroxylamine. Two anodic waves appeared at +1.32 V and +1.53 V. The first electron uptake for LQB‐569 occurs in the nitroaromatic group, followed by reductions to give a more electrophilic nitroso, prone to dimerizing and forming reducible azoxy derivatives, along with nitrone reduction, in a 10‐electron total process. One irreversible anodic wave at +1.45 V appears, related to the nitrone oxidation. The electrochemical oxidation profile can be correlated to antioxidant capacity (AO). The ability to scavenge 2,2‐diphenil‐1‐picrylhydrazyl (DPPH)• radicals (% radical scavenging activity) and reduce ferric complexes (ferric‐reducing antioxidant power) were used to assess. LQB‐569 showed low AO, due to the presence of the electron‐withdrawing group, reflecting the oxidative part of the CVs.